2020
DOI: 10.22376/ijpbs/lpr.2020.10.5.p6-10
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Pharmacist Counselling On Knowledge, And Medication Adherence In Tuberculosis Patients: A Quasi-Experimental Design

Abstract: Medication adherence and knowledge towards tuberculosis management are very important to cure and to prevent resistant tuberculosis. The study aims to evaluate the impact of pharmacist delivered counseling services on knowledge and medication adherence levels of tuberculosis patients. This is a quasi-experimental design without control conducted in an infectious unit of a secondary care referral hospital located in rural settings of Anantapur district, India. The study protocol was approved by the institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Table 1 provides an overview of the included studies. Six studies originated from high-TB-burden countries, including four from India (Bhardwaja et al, 2012;Venkatapraveen et al, 2012;Thomas et al, 2018;Narayana et al, 2020), one from China (Tang et al, 2018), and one from Indonesia (Karuniawati et al, 2019). Others were from different regions: Thailand (Tanvejsilp et al, 2018), Ivory Coast (Abrogoua et al, 2016), Türkiye (Clark et al, 2007), andBrazil (Lopes et al, 2017).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 provides an overview of the included studies. Six studies originated from high-TB-burden countries, including four from India (Bhardwaja et al, 2012;Venkatapraveen et al, 2012;Thomas et al, 2018;Narayana et al, 2020), one from China (Tang et al, 2018), and one from Indonesia (Karuniawati et al, 2019). Others were from different regions: Thailand (Tanvejsilp et al, 2018), Ivory Coast (Abrogoua et al, 2016), Türkiye (Clark et al, 2007), andBrazil (Lopes et al, 2017).…”
Section: Study Selectionmentioning
confidence: 99%
“…Notably, among the 10 studies, no randomized controlled studies were identified. Study designs were heterogeneous and included five prospective cohort studies (50%) (Bhardwaja et al, 2012;Venkatapraveen et al, 2012;Lopes et al, 2017;Tanvejsilp et al, 2018;Thomas et al, 2018), two case-control studies (20%) (Clark et al, 2007;Tang et al, 2018), two quasi-experimental studies (with and without control) (Karuniawati et al, 2019;Narayana et al, 2020), and a cross-sectional study (Abrogoua et al, 2016). Most studies were prospective; for only one study, this was unknown (Abrogoua et al, 2016).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usual care (Goruntla et al, 2020) Patients are given counseling with education regarding the etiology, signs and symptoms, modes of transmission, and complications of tuberculosis. Patients were also educated about antitubercular therapy, duration, possible side effects, and the importance of medication adherence using brochures.…”
Section: Routinementioning
confidence: 99%